Production of dicarboxylic acid platform chemicals using yeasts: focus on succinic acid - Pais, Célia (2016)
The biotechnological production of biobased dicarboxylic acids has recently become a hot topic in industrial biotechnology, with many investments involved in the development, piloting, and validation at demonstration scale of diverse processes using renewable raw materials. This chapter will review the main markets and applications of commercially relevant dicarboxylic acids and will briefly present their current chemical and biotechnological production processes. The chapter will mainly focus on the particular case of succinic acid. The microbial platforms that have been proposed will be reviewed with emphasis on yeast strains. The basic requirements for setting up and scaling the bioprocess and the required purification strategy to obtain an economically feasible process yielding a product meeting the required specifications will be presented. Throughout the chapter, the specific challenges of using very low-cost raw materials such as agro-industrial residues will be highlighted.